SOCIOLOGY OF THE AUTHOR IN THE POEM “AKU” BY CHAIRIL ANWAR - Padang, Taufik Febriansah; Nasution, Dea Octavia; Br Sebayang, Dea Shintya; Nabila, Nabila; Br Tambunan, Indah Sari (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2023)
The poem